The Contribution of Cultural Intelligence on Reducing Job Burnout and the Moderating Role of Perceived Organizational Support - Bui Nhat, Vuong (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2024)
The objective of this study is to test the relationship between cultural intelligence (CQ) and job burnout (JB) through the mediating role of team relationship conflict (RC). Besides, the moderating role of perceived organizational support (POS) is also considered. Surveyed data from 151 Vietnamese flight attendants working for 10 foreign airlines (Japan Airlines, Korean Air, Asiana Airlines, T'way Air, Eva Air, Emirates Airlines, Lufthansa, Finnair, Kenya Airways, và China Airlines) were collected and analyzed using the PLS-SEM model with SmartPLS 4.0 software. Results showed that flight attendants with higher cultural intelligence have lower job burnout. Additionally, this negative relationship was partially mediated by team relationship conflict. Furthermore, the finding has also confirmed the moderating role of perceived organizational support. When flight attendants have high CQ and receive organizational support, Job burnout is improved. Finally, the study also proposed some implications for aviation managers in reducing job burnout among flight attendants.
Keywords: Cultural intelligence; Job burnout; Team relationship conflict; Perceived organizational support; Vietnamese flight attendants